RESOURCES AND POTENTIAL OF AGRI-FOOD PRODUCTS WITH ADDED VALUE IN BRANIČEVO-PODUNAVLJE REGION - Mihailović, Branko; Radić Jean, Ivana (Economics of Agriculture, 2019)
The paper explores the agricultural resources of the Braničevo-Podunavlje region and opportunities of agri-food products development with added value. The purpose of the research is to examine the real possibilities for the development of agriculture and rural areas of the Region through the added stages of processing of agro-food products. In the research was used spatial and sectoral analysis of agricultural resources and potential. The research’s results show that the use of comparative advantages and traditions, which the BP region has in the field of agricultural production presupposes the transformation of domestic agriculture and all forms of business entities in this activity. In the coming period, emphasis must be placed on the development of agri-food products with added value, which is focused on meeting the needs and wishes of consumers, with an emphasis on innovation, quality, high level of food hygiene and food safety standards.